A semi-nested PCR assay for molecular detection of Paracoccidioides brasiliensis in tissue samples - Koishi, Andrea Cristine (2010)
INTRODUCTION: Paracoccidioidomycosis is a systemic infection caused by Paracoccidioides brasiliensis. METHODS: In this study, a semi-nested PCR for paracoccidioidomycosis diagnosis was developed. The primers ITS1 and ITS4 were used in the first reaction, while the primers MJ03 and ITS1 primer were used in the second reaction. The semi-nested PCR was used to investigate biopsies of five patients with oral lesions that resembled paracoccidioidomycosis. RESULTS: The semi-nested PCR was positive for four samples and negative for a sample from a patient later diagnosed with leishmaniasis. CONCLUSIONS: The new semi-nested PCR describe is useful for aracoccidioidomycosis diagnosis. ________________________________________________________________________________________________________________ RESUMO